Thinking about a war-image: visual testimony and resistance strategy in works by Rabih Mroué, Harun Farocki and Tania Bruguera - Elias, Mariana Teixeira (Farol, 2024)
This article analyzes the use of images by artists such as Rabih Mroué, Harun Farocki and Tania Bruguera, highlighting their role in documenting reality, communicating messages and acting as a form of resistance. We investigated how their approaches contribute to the engagement and interpretation of conflicts, forming the concept that we call “image-war”, inspired by the ideas of Paul Virilio, discussed in the book War and Cinema. The article highlights the relevance of the image in the contemporary visual, social and political spheres.